Compositional and structural changes of sugarcane evaporator deposits after concentrated sodium hydroxide treatment. (December 2017) - Phakam, Bunnaporn; Moghaddam, Lalehvash; Baker, Adrian G.; East, Christopher; Doherty, William O.S.
Abstract: Fouling of industrial heat exchangers and evaporators is not only associated with energy management but also reductions in heat transfer coefficients causing loss in productivity. This paper describes the effect of NaOH solution on the removal of sugarcane factory heat exchanger deposits. Apatite, calcium oxalate, calcite, quartz, tricalcium aconitate and non-diffracting materials including amorphous silica are present in the deposits. Fourier Transform Infra-red (FTIR) spectroscopy revealed that monomeric silica species were preferential removed over oligomeric and polymeric species, while 29 Si nuclear magnetic resonance (NMR) analysis not only confirmed this, but identified the types of silica units Q 0 [Si(OH)4 ], Q 1 [(OH)3 *Si(OSi)], Q 2 [(OH2 *Si(OSi)2 ], Q 3 [(OH)*Si(OSi)3 ] and Q 4 [*Si(OSi)4 ] present, rearranged, and removed. After chemical cleaning, the scale components became truncated with indentation and contain spherical and hairy-like micro-sized particles. Also, the morphology of tetragonal CaCO4 ·2H2 O was found to be distorted and the proportion of crystalline phases decreased through fragmentation of the scale matrix. Highlights: The preferential removal of monomeric over polymeric silica network by NaOH. The effect of NaOH solution on the transformation of evaporator scale. The identification of different types of silica species in heat exchanger deposit. The identification of tricalcium aconitate trihydrate in sugarcane scale deposit. The use of 29 Si magic angle spinning NMR to evaluate heat exchanger scale.